Control process of safety occupational health and environmet management through the application of a web system - Alonzo Gomero, Nadia Violeta (2022)
Deaths due to occupational accidents have motivated organizations to implement occupational health and safety management systems as a measure to prevent the occurrence of accidents. This research proposes that the implementation of a management system generates large volumes of information and commitments that require timely attention, therefore, to achieve better results, effective tools are needed to manage information, in that sense, a computer application developed for a web environment was implemented in the process of control of safety, occupational health and environment, then through interviews with those responsible for the process, describe the effects and perceptions on results of the use of office automation tools and web application. For this purpose, the research was carried out at a descriptive level, qualitative approach, non-experimental, cross-sectional design. The research concludes that using Office tools to control a management system is insufficient to process and analyze large volumes of information; however, using web applications, in addition to eliminating time, volume and distance limitations, their continuous availability from any PC or mobile device with internet access, facilitates the definition of strategies and decision making in time to prevent accidents.